Efektivitas Media Pembelajaran Information And Communication (ICT) Pada Mata Pelajaran Pendidikan Agama Islam di SMPM 2 Balongpanggang - Dandi Anggriawan; Noor Amirudin; Man Ode Arfa Ladamay (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research is motivated by technological advances in the 4.0 era. With these technological advances, teachers must have the ability to use learning technology. So in this study, researchers examined the effectiveness of ICT learning media in Islamic Religious Education subjects at SMPM 2 Balongpanggang. This research aims to find out how effective ICT learning media is in Islamic Religious Education subjects at SMPM 2 Balongpanggang. The method used is quantitative. The population in this study was 21 students. The sample used in the research was 21 students. Data collection techniques use questionnaires. The data analysis technique uses simple linear regression